PENERAPAN MEDIA SOFTWARE INTERAKTIF SEBAGAI MEDIA EDUKASI DALAM PERUBAHAN TINGKAT PENGETAHUAN DAN PERILAKU KESEHATAN GIGI SERTA TINGKAT KEBERSIHAN GIGI - Ani Subekti; Bambang Sutomo; Bedjo Santoso; Salikun Salikun; Rizki Amalia; Ratna Puspita; Kharismana Umia (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2018)
The structure of teeth in childhood, early childhood is the period of milk teeth are susceptible to dental caries. Dental caries is the formation of holes in the tooth surface caused by germs and open gear formed on the surface that is associated dental crown dental health maintenance behaviours are influenced by factors outside the individual and the individual. The purpose of community service has Occurred change the level of knowledge and behaviour about oral health and oral hygiene level of the child - the child early childhood Pearl Pedurungan after being given counselling using an interactive software as a medium of education.Implementation methods devotion this by combining several stages of activities, namely: Taking the initial data by performing a dental hygienist, the level of knowledge of children and toothbrushing behavior to the target, Stage interventions: Counseling Program software, Demonstration brushing, Monitoring during the week and two weeks with the observation of parents at home, data retrieval end of the examination of dental hygiene, knowledge and behavior of children brushing teeth and mouth to the target return.Application of audiovisual media using a software extension can provide a change in the level of dental hygiene, dental health knowledge and toothbrushing behaviour in children early childhood Pedurungan Pearl District of Semarang. Media education on dental health software that is applied in the Post ECD Pearls can be used as a learning program in the field of dental health.